P 55. Epidemiology, Healthcare Resource Use, and Mortality in Patients with Tuberous Sclerosis Complex: A Population-Based Study on German Health Insurance Data. Issue 8 (August 2021) - Strzelczyk, A.; Schubert-Bast, S.; Zöllner, J.P.; Simon, A.; Wyatt, G.; Holland, R.; Rosenow, F.
Abstract : Introduction. Retrospective, 10-year (2007−2016) study reporting prevalence, patient characteristics, cost, hospitalisation, length of stay (LOS), medication, and mortality for patients with tuberous sclerosis complex (TSC), a rare, multisystemic, genetic disorder. Methods. Patients with TSC were identified from the German Vilua Healthcare research database (anonymised health insurance data for >4 million individuals) using International Classification of Disease (ICD)-10 code Q85.1. Epilepsy was identified by ≥1 epilepsy ICD code (G40*/G41*) or ≥1 antiepileptic drug (AED) prescription after TSC diagnosis. Mortality was compared with age-, sex-, and time-matched controls. Results. In 2016, 100 patients with TSC (mean [range] age: 38 [1–86] years; male: 40%) were identified. Standardised prevalence of TSC was 7.9 per 100, 000 people and 2.2 per 100, 000 for TSC with epilepsy. Other TSC manifestations and comorbidities (apart from epilepsy) were identified more frequently in patients with epilepsy than in those without. From 2007−2016, mean annual healthcare costs were €6, 139 per patient-year (PPY), mostly attributable to medication (€2, 144, 35%) and inpatient care (€1, 807, 29%). Patients with epilepsy incurred greater total annual costs than those without (€9, 091 vs. €4, 583 PPY). Mean (SD; range) annual hospitalisation rate (all TSC patients) was 0.5 (1.0; 0–9) with LOS 5.9 (18.6; 0–264) days PPY. Mean (SD; range) annual hospitalisation rate was numerically greater in patients with epilepsy than without (0.7 [1.2; 0–8] vs. 0.4 [0.8; 0–9]) PPY), as was LOS (8.4 [21.4; 0–183] vs. 4.6 [16.8; 0–264] days PPY). In patients with TSC, mean (SD; range) number of different medications prescribed: 6.3 (5.1; 1–33) PPY and 19.2 (14.4; 1–83) per patient over the entire observable time. In patients with TSC and epilepsy, 3 (2.3; 1–11) different AEDs were prescribed over the entire observable time. Mortality rates (vs. control): all TSC 5.08% (1.69%), p<0.001; with epilepsy 7.53% (0.98%), p<0.001; without epilepsy 3.68% (2.03%), p=0.003. Conclusions . Healthcare costs, resource utilisation and mortality were higher in patients with TSC and epilepsy versus those without. Occurrence of epilepsy in patients with TSC was lower than previously reported; population-based, rather than epilepsy centre-based, patient selection may somewhat explain this finding. Patients without epilepsy had a lower incidence of TSC-related manifestations indicating a milder TSC cohort, which may be a result of increased familial genetic screening in Germany.